Reliability and validity of a new accelerometer (Wimu®) system for measuring velocity during resistance exercises - Muyor, J. M.; Granero-Gil, P.; Pino-Ortega, J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2018)
This study had two main goals. The first was to determine the reliability of the Wimu system (accelerometer) for mean velocity measurements during resistance exercises at 40% and 80% 1 repetition maximum (1RM). The second was to compare the results for the Wimu system to a linear encoder (gold standard) for mean velocity measurements when clipped to the bar during back squat exercises using the Smith machine. In all, 23 trained men (aged 22.3 ± 3.2 years) participated in this study. At maximum velocity in the concentric phase, they performed 10 repetitions with 40% 1RM and eight repetitions with 80% 1RM while using the Wimu system and T-Force linear encoder simultaneously to record data. Reliability was analysed using intraclass correlation, standard error of measurement and coefficient of variation. The validity was assessed using R2, intraclass correlation and Bland-Altman plots. The differences in test-retest reliability of both systems and systematic biases were non-significant (p = 0.08-0.85) and very close to 0. The random errors averaged ±0.010 m/s. All the calculated coefficient of variations were less than 5% and all measurements had high intraclass correlations (mean: 0.936). Least-square linear regression and intraclass correlations for validity were very close to 1. Significant systematic biases were observed between the linear encoder and the Wimu system (p < 0.001), although the effect sizes were small (0.21 0.44) and standard error of the estimate in concentric and eccentric phases at both intensities was less than 0.030. In conclusion, the findings of this study suggest that the Wimu system is a reliable and valid tool for the assessment of mean velocity during the back squat exercise using the Smith machine. These findings could help coaches and sport researchers evaluate athletes performing resistance exercises similar to squats with a reliable, valid and portable tool.